Ecosystem processes are rarely included in tactical fisheries management. Issue 1 (22nd January 2015) - Skern‐Mauritzen, Mette; Ottersen, Geir; Handegard, Nils Olav; Huse, Geir; Dingsør, Gjert E; Stenseth, Nils C; Kjesbu, Olav S
Abstract: Fish stock productivity, and thereby sensitivity to harvesting, depends on physical (e.g. ocean climate) and biological (e.g. prey availability, competition and predation) processes in the ecosystem. The combined impacts of such ecosystem processes and fisheries have lead to stock collapses across the world. While traditional fisheries management focuses on harvest rates and stock biomass, incorporating the impacts of such ecosystem processes are one of the main pillars of the ecosystem approach to fisheries management (EAFM). Although EAFM has been formally adopted widely since the 1990s, little is currently known to what extent ecosystem drivers of fish stock productivity are actually implemented in fisheries management. Based on worldwide review of more than 1200 marine fish stocks, we found that such ecosystem drivers were implemented in the tactical management of only 24 stocks. Most of these cases were in the North Atlantic and north‐east Pacific, where the scientific support is strong. However, the diversity of ecosystem drivers implemented, and in the approaches taken, suggests that implementation is largely a bottom‐up process driven by a few dedicated experts. Our results demonstrate that tactical fisheries management is still predominantly single‐species oriented taking little account of ecosystem processes, implicitly ignoring that fish stock production is dependent on the physical and biological conditions of the ecosystem. Thus, while the ecosystem approach is highlighted in policy, key aspects of it tend yet not to be implemented in actual fisheries management.